PENINGKATAN KONSEP BERHITUNG ANAK MELALUI METODE PEMBERIAN TUGAS DI KELOMPOK B PADA TK AISYIYAH BUSTANUL ATHFAL 3 KECAMATAN SAMARINDA ULU TAHUN PEMBELAJARAN 2017 / 2018 - Erdalina - Erdalina (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
It is important to start learning mathematic with concept of calculation naturally through playing. So that, the young learners are able to find examine and explain the mathematic concept throught their daily activities. The researcher conducted a classroom action research in group B at AisyiyahBustanulAthfal 3 Kindergarten to improve student’ ability in understanding concept of calculation through task-based learning method. The researcher applied two cycles with four stages; planning; implementation, observation and reflection. Seventeen students were also involved as the research subject. To collect the data, the researcher employed observation sheet and student activity sheet. The data was analyzed through the increasing average score. It can be proved from the first cycle, students’ ability developed very well at 32%, developed as expected at 58,5%, and started to developed at 30,28%. Meanwhile, in the second cycle, 53,8% students developed very well, 32,3% developed as expected and 15% started to developed. Based on the calculation of percentages in cycle 1 and 2, the average percentage in cycle 1 was 35,1% and cycle 2 was 83,7%. In brief, the task-based learning has effectively increased students’ ability in understanding concept of calculation with learning topic “myself” and improved student’ learning activities.